A.V.H. Hartendorp papers - Hartendorp, A. V. H.; Hartendorp, A. V. H.; Hartendorp, A. V. H.; Hartendorp, A. V. H.
Writings by Hartendorp including typescripts of his memoirs, I Have Lived: Reminiscences of A.V.H. Hartendorp; a book, The Japanese Occupation of the Philippines (1967), pertaining to his internment in the Santo Tomas Internment Camp, Manila, Philippines; and a collection of unpublished poems titled "This Mortal Coil." Also includes a printed copy of his book A Few Poems and Essays (1951).
Author, journalist, and editor. Full name: Abram (Abraham) van Heyningen Hartendorp. Born 1893.
Collection material in English.
Keywords: Santo Tomas Internment Camp (Manila, Philippines); Poetry; World War, 1939-1945 -- Concentration camps -- Philippines; World War, 1939-1945 -- Prisoners and prisons, Japanese; Philippines -- History -- Japanese occupation, 1942-1945.; Authors; Editors; Journalists